Transoral endoscopic excision of cystic hygroma vestibular approach in adult (novel approach): a case report - Gajbhiye, Raj N.; Kharkate, Ganesh K.; Tirpude, Vidhey S. (International Surgery Journal, 2020)
Lymphangioma, soft tissue tumor was originally reported by R. Backer in 1828 and “cystic hygroma” name was first given by Wernker in 1834. It can occur in the head, neck, axilla, cervico-facial regions and below tongue. Although it is well recognized in children, it may present in adulthood. Cystic hygroma neck is traditionally removed via an overlying incision near or over the swelling. The resultant scar can be displeasing to an adult. Various endoscopic approach present in literature for excision are via neck, anterior chest, combined or robotic assisted. We here, are reporting transoral endoscope excision of cystic hygroma via vestibular approach. A 51 year old female with swelling over anterior aspect of neck, trans-illumination positive, diagnosis confirmed on CT neck, of size 4×4 cm was our case. We decided for transoral endoscopic vestibular approach for excision, first of its kind with no assisted approach. Patient discharged after 3 post-operative days (PODs). There was mild seroma which resolved within a week. Transoral endoscopic excision of cystic hygroma via vestibular approach without any assisted approach can be applied in adult. Various approach present in literature for excision of cystic hygroma are via neck, anterior chest or combined or robotic assisted. Hence this approach can be an excellent choice for adult cystic hygroma patients who desire to avoid a neck incision. Transoral endoscopic excision of cystic hygroma via vestibular approach was successfully performed. Patient was satisfied with good cosmosis. It results in good cosmesis and better dissection. Hence can be a new method of excision of cystic hygroma in adult.